Multidrug-Resistant Lineage of Enterotoxigenic Escherichia coli ST182 With Serotype O169:H41 in Airline Waste - Jarocki, Veronica M.; Heß, Stefanie; Anantanawat, Kay; Berendonk, Thomas U.; Djordjevic, Steven P. (Frontiers in Microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) is the primary aetiologic agent of traveller’s diarrhoea and a significant cause of diarrhoeal disease and death in developing countries. ETEC O169:H41 strains are known to cause both traveller’s diarrhoea and foodborne outbreaks in developed countries and are cause for concern. Here, whole-genome sequencing (WGS) was used to assemble 46 O169:H41 (ST182) E. coli draft genomes derived from two airplane waste samples sourced from a German international airport. The ST182 genomes were compared with all 84 publicly available, geographically diverse ST182 genomes to construct a core genome-based phylogenetic tree. ST182 isolates were all phylogroup E, the majority serotype O169:H41 (n = 121, 93%) and formed five major clades. The airplane waste isolates differed by an average of 15 core SNPs (range 0–45) but their accessory genome content was diverse. While uncommon in other ST182 genomes, all airplane-derived ST182 isolates carried: (i) extended-spectrum β-lactamase gene blaCTX–M–15 notably lacking the typical adjacent ISEcp1; (ii) qnrS1 and the S83L mutation in gyrA, both conferring resistance to fluoroquinolones; and (iii) a class 1 integron structure (IS26-intI1Δ648-dfrA17-aadA5-qacEΔ1-sul1-ORF-srpC-padR-IS6100-mphR-mrx-mphA-IS26) identified previously in major extraintestinal pathogenic E. coli STs but not in ETEC. ST182 isolates carried ETEC-specific virulence factors STp + CS6. Adhesin/invasin tia was identified in 89% of aircraft ST182 isolates (vs 23%) and was located on a putative genomic island within a hotspot region for various insertions including PAI I536 and plasmid-associated transposons. The most common plasmid replicons in this collection were IncFII (100%; F2:A-:B-) and IncB/O/K/Z (89%). Our data suggest that potentially through travel, E. coli ST182 are evolving a multidrug-resistant profile through the acquisition of class 1 integrons and different plasmids.